PENDAMPINGAN PASTORAL BAGI KAUM LANSIA DI PANTI WERDA DAMAI RONOMUUT - Frieska Putrima Tadung; Merry Regina Mamuko; Remalia Putri Matsino (Institut Agama Kristen Negeri Manado, 2022)
Elderly or commonly referred to as elderly is someone who has entered the final stages of the life phase. Elderly is an advanced stage of a life process characterized by a decrease in the body's ability to adapt to environmental stress. The aging process is characterized by visible and invisible physiological changes. In old age there are several problems faced by the elderly, namely, economic problems, social problems, health problems, psychosocial problems, and changes in interest in old age. The problem of interest and desire in the elderly is one of the most disturbing problems for themselves and those around them. Pastoral ministry takes a big place in supporting the existence of the elderly. Pastoral Accompaniment Service is a dimension of the church that needs to be carried out bearing in mind that throughout its life span, people will not be separated from crises or unexpected problems. Mentoring or accompanying is an activity that can help counselees. In this elderly period requires special attention, because of the increasingly weak physical abilities and various diseases that the elderly may suffer. The approach in this study is to use this research usingdescriptive qualitative which seeks to describe a social phenomenon. The object of research is the elderly in the Ranomuut Nursing Home.